Patient Satisfaction Analysis Based on Gronroos Method at Obstetric-Gynecology Specialist Clinic, Mitra Keluarga Waru Hospital, Sidoarjo - Hartatie Hartatie; Setya Haksama (Humanistic Network for Science and Technology (HNST), 2018)
Specialist clinic of Obstetric and Gynecology care of Mitra Keluarga Waru Hospital is a service that needed by the community and contributes to the decreasing of Maternal and Infant Mortality Rate. Health and growing fetus was very important care service, it needs to be monitored its growth during pregnancy. Based on these conditions, Mitra Keluarga Waru Hospital should always maintain and improve the quality of service. One of the steps is to measure the level of patient satisfaction. The purpose of this research was to analyze the effect of service quality based on Gronroos Method that consisting of professionalism and skills, behaviour and attitudes, accessibility and flexibility, reliability and trustworthiness, recovery, reputation and credibility to patient satisfactionin Mitra Keluarga Waru Hospital Sidoarjo. The population was outpatients who use services, and sample of 30 people. Collecting data using questionnaires and documentary study. Data analysis techniques using descriptive statistics with Frequency distribution, all dimension was on “Very Satisfied” category. Then the research showed: Professionalism and skills Score 671 and Average 4.47; Reliability and trustworthiness Score 654 and Average 4.36; Behaviour and Attitudes Score 763 and Average 4.24; Accessibility and Flexibility Score 665 and Average 4.43; Service recovery Score 381 and Average 4.23; and Reputation and Credibility Score 524 and Average 4.37. Recommendation is to improve services through training to all staff including medical doctors, give reward to employees, and system information development Keywords: Patient satisfaction; Gronross method